Implementasi Proses Rekrutmen dan Seleksi pada PT Angkasa Indo Jaya - Go, Michelle; Dini, Yuli Indah Fajar (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
The process of recruitment and selection is an important procedure in an effort to attract qualified candidates who meet the job qualifications of a company. This practical work activity aims to analyze the challenges faced by PT Angkasa Indo Jaya as a manpower supply company, when they are getting large projects from their clients. The result of the observation found that PT Angkasa Indo Jaya tends to still have applicants who do not meet the job qualification requirements. In an effort to attract extra manpower capable of contributing to several departments of the company, the outputs of the activity that have been designed include a recruitment and selection strategy flowchart, job description, and candidate evaluation form. The implementation of the activity’s outcomes on PT Angkasa Indo Jaya has succeeded in facilitating the work of the Human Resources (HR) department in the process of recruiting and selecting prospective employees who have met the qualification requirements.